ACESSO À ARQUITETURA E ASSISTÊNCIA TÉCNICA PARA MORADIAS DE BAIXA RENDA - Pereira, Gabriella Leles; Paula, Kenia Alves de (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
Much of the production of housing in Brazil occurred through informal methods as result of selfconstruction. The lack of buildings advised by a professional ended up generating alarming data on the lack of adequate housing conditions in the peripheries of every country. This research seeks to identify factors, in addition to financial issues, that distance the low income population from access to architecture and basic quality housing, seeking to address discussions about the lack of knowledge of the rights themselves, the positive effects of technical assistance, and how this can be blended with self-construction so that it does not lose the essence of the empirical knowledge and desire of each inhabitant over his work, a strong characteristic in the culture of self-construction.